Design of Short Circuit Detection and Destruction Equipment for Electronic Components and Circuits - Al-Amin, Imam Ma'ruf; Subarwanti, Yunita; Rikarda, Willy Artanika (Indonesian Journal of Advanced Research, 2024)
This research aims to design and understand the working principles of short circuit detection and destruction devices in electronic circuits and components. The short circuit detector and destroyer uses a voltage injection method which is applied to the electronic circuit path and detects short components. Changes in temperature, voltage and current values produced by the DC Buck Converter were observed using supporting fluids, namely rosin and wax. The results obtained on electronic components and circuits are more efficient using liquid wax compared to liquid rosin (Flux). This tool is designed to use a DC Buck Converter as the main circuit and a Volt Meter as a voltage display and can be used effectively to detect short circuits, check DC voltage values, source DC voltage input and increase the voltage value on the battery (1.3-12 VDC).